Educational Inclusion of Students with Disabilities in Situations of Social Vulnerability - de Paula, Elifas Trindade; Del-Masso, Maria Candida Soares [UNESP] (Springer Nature, 2023)
The main objective of this research was to understand the factors that interfere in the activities of teachers dealing with special education service, concerning areas of social vulnerability. To delineate the social vulnerability condition, we have considered the concepts of social class and crisis, taking into account classical works of Marx and Engels. Considering this referential, it becomes clear that the social vulnerability is a contradiction of the capitalist society. Aside from its huge productive ability, it is not able to offer worthy conditions of life for most of the population to read the main goal. Hence, we have chosen to hear the professionals that work as teachers of special education service, with half-structured interviews. To know better the work conditions, we realized the interviews “in loco,” taking notes as observations that allowed us to consider the material and human conditions of the places where the attendance happens. After collecting the data, we have organized a category analysis, considering the main factors that interfere on the work of experts that attend special education target students and performed a qualitative analysis. First, we have detached work conditions, family situations, and vulnerability. After, considering the public policy, we analyzed the support offered by equipment available in the community. The results have shown that even with equipment’s and furniture available multifunctional classes and resources, the structural conditions and vulnerability conditions interfere negatively on the teacher’s performance; the public health equipment is insufficient for demand fulfillment, and there is few informational and articulation with leisure, sport, and culture. Concerning the public policy, the data reveal that many times the schoolwork in isolation in the conclusion process. Finally, this research has shown that special education target students have the school as the only resource since other different services are lacking in socially vulnerable areas.